2000
DOI: 10.1038/sj.bmt.1702408
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ selection of autologous peripheral blood stem cells for transplantation following sequential cycles of high-dose therapy and mobilisation in multiple myeloma

Abstract: Summary:A potential problem of autologous transplantation in the treatment of multiple myeloma (MM) is the infusion of tumor cells. CD34 + selection has been used to purge autografts in MM and it is also possible to reduce tumour cell contamination of autografts by cytotoxic drug therapy prior to peripheral blood stem cell (PBSC) collection. To evaluate the effectiveness of a protocol combining multiple cycles of high-dose therapy and CD34 + selection to reduce tumour contamination of PBSC autografts, 34 MM pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…However, since myeloma cells do not express the CD34 antigen, 9,10,11 positive selection of CD34 + hematopoietic progenitor cells 12,13,14 has been used as a means of myeloma cell "purging" in ASCT. 11,15,16 In 1995, we initiated a European Group for Blood and Marrow Transplantation (EBMT) centre phase III randomized study to assess the safety and efficacy of CD34+ selection compared to unselected PBPC in patients with myeloma undergoing autologous transplantation. A similar study was initiated at around the same time in the United States, the preliminary results of which suggested that at a median follow-up of 12 months there was no clinical benefit from CD34 + selection.…”
mentioning
confidence: 99%
“…However, since myeloma cells do not express the CD34 antigen, 9,10,11 positive selection of CD34 + hematopoietic progenitor cells 12,13,14 has been used as a means of myeloma cell "purging" in ASCT. 11,15,16 In 1995, we initiated a European Group for Blood and Marrow Transplantation (EBMT) centre phase III randomized study to assess the safety and efficacy of CD34+ selection compared to unselected PBPC in patients with myeloma undergoing autologous transplantation. A similar study was initiated at around the same time in the United States, the preliminary results of which suggested that at a median follow-up of 12 months there was no clinical benefit from CD34 + selection.…”
mentioning
confidence: 99%
“…No quality-of-life benefit was apparent during the first 2 years, and after 2.5 years, there was a trend only. 31 The MRC trial has just been published, comparing standard therapy consisting of ABCM (doxorubicin, BCNU, cyclophosphamide, melphalan) every 6 weeks or C-VAMP (cyclophosphamide, vincristine, doxorubicin, methylprednisolone) every 3 weeks followed by mobilization with cyclophosphamide 2 to 4 g/m 2 For personal use only. on April 29, 2019.…”
Section: What Other Evidence Is There?mentioning
confidence: 99%
“…In an attempt to reduce tumor cell contamination, various CD34 ϩ selection methodologies have been reported. [29][30][31]79 None of these trials have demonstrated an improvement in PFS or OS. Allotransplantation provides 2 distinct advantages: absence of contaminating tumor cells in the autograft and the benefit of alloreactive donor T lymphocytes producing a GVM effect.…”
Section: Allogeneic Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 Different physical, clinical, and immunologic means have been used to purge the contaminating tumor cells ex vivo, including the use of activated autologous NK cells to overcome relapse. [48][49][50][51][52] In our previous report investigating the possibility of syngeneic NK cells as purging agents in a murine leukemia model, we demonstrated that blocking inhibitory receptors specific for class I on a subset of syngeneic NK cells during ex vivo purging of C1498 murine leukemia contaminating the bone marrow graft significantly increased the extent of tumor cell elimination by syngeneic NK cells. 53 We also demonstrated that transplanting tumorcontaminating BMCs purged with syngeneic NK cells with inhibitory receptor blockade resulted in an increased proportion of long-term survivors without affecting hematopoietic cell recovery.…”
Section: Introductionmentioning
confidence: 99%